Effect of Physical Training on Exercise-Induced Inflammation and Performance in Mice - Barcellos, Luiz Alexandre Medrado de; Gonçalves, William Antonio; Esteves de Oliveira, Marcos Paulo; Guimarães, Juliana Bohnen; Queiroz-Junior, Celso Martins; Resende, Carolina Braga de; Russo, Remo Castro; Coimbra, Cândido Celso; Silva, Albená Nunes; Teixeira, Mauro Martins; Rezende, Barbara Maximino; Pinho, Vanessa (Frontiers in Cell and Developmental Biology, 2021)
Acute exercise increases the amount of circulating inflammatory cells and cytokines to maintain physiological homeostasis. However, it remains unclear how physical training regulates exercise-induced inflammation and performance. Here, we demonstrate that acute high intensity exercise promotes an inflammatory profile characterized by increased blood IL-6 levels, neutrophil migratory capacity, and leukocyte recruitment to skeletal muscle vessels. Moreover, we found that physical training amplified leukocyte–endothelial cell interaction induced by acute exercise in skeletal muscle vessels and diminished exercise-induced inflammation in skeletal muscle tissue. Furthermore, we verified that disruption of the gp-91 subunit of NADPH-oxidase inhibited exercise-induced leukocyte recruitment on skeletal muscle after training with enhanced exercise time until fatigue. In conclusion, the training was related to physical improvement and immune adaptations. Moreover, reactive oxygen species (ROS) could be related to mechanisms to limit aerobic performance and its absence decreases the inflammatory response elicited by exercise after training.